Identification of New L-Heptanoylphosphatidyl Inositol Pentakisphosphate Derivatives Targeting the Interaction with HIV-1 Gag by Molecular Modelling Studies - Halilibrahim Ciftci; Belgin Sever; Esra Ayan; Mustafa Can; Hasan DeMirci; Masami Otsuka; Amaç Fatih TuYuN; Hiroshi Tateishi; Mikako Fujita (MDPI AG, 2022)
The HIV-1 Gag protein binds to the host cell membrane and assembles into immature particles. Then, in the course of immature virion budding, activated protease cleaves Gag into its main components: MA, CA, NC, and p6 proteins. The highly basic residues of MA predominantly interact with the acidic head of phosphatidyl-inositol-4,5-bisphosphate (PI(4,5)P2) inserted into the membrane. Our research group developed L-Heptanoylphosphatidyl Inositol Pentakisphosphate (L-HIPPO) and previously confirmed that this compound bound to the MA more strongly than PI(4,5)P2 and inositol hexakisphosphate (IP6) did. Therefore, herein we rationally designed eight new L-HIPPO derivatives based on the fact that the most changeable parts of L-HIPPO were two acyl chains. After that, we employed molecular docking for eight compounds via Maestro software using high-resolution crystal structures of MA in complex with IP6 (PDB IDs: 7E1I, 7E1J, and 7E1K), which were recently elucidated by our research group. The most promising docking scores were obtained with benzene-inserted compounds. Thus, we generated a library containing 213 new aromatic group-inserted L-HIPPO derivatives and performed the same molecular docking procedure. According to the results, we determined the nine new L-HIPPO derivatives most effectively binding to the MA with the most favorable scoring functions and pharmacokinetic properties for further exploration.